Formulation of Biscuit Using Yellow Pumpkin Flour and The Addition of Coconut Flour as an Alternative for Complementary Feeding - Mauren Gita Miranti; Dwi Kristiastuti; Endah Dwi Kusumasari (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
Complementary food should be added to the diet of the babies in addition to breast milk from 6 months onward and the food should be sufficient for the baby’s nutrition needs. Complementary feeding using baby biscuit made of yellow pumpkin flour and the addition of coconut flour is an effort to improve nutrition through local food diversification approach. The purpose of this study was to determine the best biscuit formulation and to test the physicochemical properties of the selected formula. This research used completely randomized experimental design consisting of four formulae of yellow pumpkin flour, i.e. 10%, 15%, 20% and 25%. The results of organoleptic tests showed that the best formula of the biscuit as complementary food is 25% yellow pumpkin flour and 12% of coconut flour. Consumption of two servings of biscuits can meet the nutritional adequacy of the babies except calcium. The biscuits can be kept for 92 days 8 hours under open conditions. In addition, the biscuits have good physical properties in terms of water absorption and hardness.